An Application of Mnemonic Strategy in the Learning of Physics at State Junior High School 7 Palembang - Sugiarti, Sugiarti (Jurnal Dosen Universitas PGRI Palembang)
Abstract -Based on information obtained from teachers whoteach science in the classroom VII Junior High School 7Palembang, that there are still reluctant learners are invitedto think analysts in physics learning materials, they seemreluctant to participate in the learning process. This isindicated by the appearance of passivity, silences justlistening to the material students are taught by a teacher.Communication that occurs is one-way communication, thatthe teacher to the student. Besides learning a monotonesystem causes boredom in students. As well as a lack ofmeaningful learning system that causes students to forgeteasily. Based on these encouraging researchers to conductresearch on the application of mnemonic strategies inlearning physics class VII Junior High School 7 Palembangon Quantities and Units of matter in the first half andhopefully with this strategy researchers can motivatestudents in learning physics and students can make it easierto remember the lessons so as to enhance learningeffectiveness in improving learning outcomes. In this studyraise the issue of how the application of mnemonic strategiesin teaching physics in class VII School 7 Palembang.Therefore, the goal of researchers is whether or not theapplication of mnemonics in learning physics strategy VIIclass in Junior High School 7 Palembang. The variables inthis study were student learning outcomes through theapplication of mnemonic strategies. The populations in thisstudy were junior high school students in grade VII at StateJunior High School 7 Palembang graders VII.3 The sampleis composed of 19 male students and 21 female students. Themethod used in this study is descriptive. Data collection wasdone by using the test. Data obtained from the tests wereanalyzed by quantitative descriptive.From the results of research and discussion is done, it can beconcluded that the study results after the Mnemonicstrategies applied on the subject of quantities and units inJunior High School 7 Palembang at the first meeting of thesub Physics and Measurement of Quantities of materialvalue is an average of 77.27 with a category of students fine.At the second meeting of the International System of Unitssub content and presentation of results of measurements anaverage value of 79.11 with a student either category. Thenon the third meeting of the final test(evaluation) the level ofstudents understanding of matter Quantities and units withan average of 87.07 with the excellent category. This suggeststhat the success rate of students with an average value ofeach meeting have increased quite good and the applicationof mnemonic strategies can be applied in the learningprocess.Keywords- application of mnemonic strategy, physics